Early life stress induces decreased expression of CB1R and FAAH and epigenetic changes in the medial prefrontal cortex of male rats - Demaili, Arijana; Portugalov, Anna; Maroun, Mouna; Akirav, Irit; Braun, Katharina; Bock, Jörg (Frontiers in Cellular Neuroscience, 2024)
Several studies in both animal models and in humans have provided substantial evidence that early life stress (ELS) induces long-term changes in behavior and brain function, making it a significant risk factor in the aetiology of various mental disorders, including anxiety and depression. In this study, we tested the hypothesis that ELS in male rats (i) leads to increased anxiety and depressivelike symptoms; and (ii) that these behavioral changes are associated with functional alterations in the endocannabinoid system of the medial prefrontal cortex (mPFC). We further assessed whether the predicted changes in the gene expression of two key components of the endocannabinoid system, cannabinoid receptor 1 (CB1R) and the fatty acid amide hydrolase (FAAH), are regulated by epigenetic mechanisms. Behavioral profiling revealed that the proportion of behaviorally affected animals was increased in ELS exposed male rats compared to control animals, specifically showing symptoms of anhedonia and impaired social behavior. On the molecular level we observed a decrease in CB1R and FAAH mRNA expression in the mPFC of adult ELS exposed animals. These gene expression changes were accompanied by reduced global histone 3 acetylation in the mPFC, while no significant changes in DNA methylation and no significant changes of histone-acetylation at the promoter regions of the analyzed genes were detected. Taken together, our data provide evidence that ELS induces a long-term reduction of CB1R and FAAH expression in the mPFC of adult male rats, which may partially contribute to the ELS-induced changes in adult socio-emotional behavior.